PENGARUH PERPUTARAN KAS,PERPUTARAN PIUTANG, PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS PADA SUPERMARKET DI TIMOR LESTE - Amaral Canizio, Matilde (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.10.TAHUN 2017, 2017)
The purpose of the study is to examine and demonstrate empirically the effect of cash turnover, receivable turnover, and inventory turnover on profitability of compnies. The date used in this study is a secondary date obtained from the compnay’s monthly financial reports during the period 2008 to 2012. Samples used are 2 Supermarket. Statistical analysis used is multiple linear regression analysis. Based on the result of analysis it can be concluded that in the cash turnover there are no significant effects on profitability in the supermarkets Leader and Lita Store. While the receivables turnover and inventory turnover have a positive effect on the profitability of the supermarket Leader and Lita